XCL1 Enhances Regulatory Activities of CD4(+)CD25(high)CD127(low/−) T Cells in Human Allergic Asthma - Nguyen, Khoa D. (2008)
Chemokine-mediated recruitment of regulatory cell subsets to the airway during inflammation and enhancement of their activities are potential strategies for therapeutic development in allergic asthma (AA). In this study, we aim to explore the role of XCL1, a chemokine associated with immune suppression and allergy, on CD4(+)CD25(high)CD127(low/−) regulatory T cell (Treg) function in AA. Flow cytometry and PCR analysis showed a reduction in XCL1 and XCR1 expression in AA Treg compared with healthy control and nonallergic asthmatic counterparts. This reduction in XCL1 expression was associated with the suboptimal regulatory function of Treg in AA. Interestingly, incubation with recombinant human XCL1 significantly increased Treg-mediated suppression and cytotoxicity by up-regulating expression of XCL1 and chief effector molecules of Treg function. Altogether, these results suggest an association between dysregulated XCL1 expression and reduced Treg activities in AA, as well as a potential role of XCL1 in reversing defective Treg function in the disease.